Innovativ e technologies of the active safety driving - A. S. Lebedeva; V. U. Maksimov (Вестник СибАДИ)
The paper deals with the essence of the safety driving concept and classification of its types. Considerable attention is paid to the concepts of active and passive safety. Based on the results of the market research the classification of innovative technologies providing transport active safety is proposed. The analysis of the existing efficiency estimation approaches of active safety systems is carried out, their disadvantages are identified. The customer-oriented methodology for comparative efficiency estimation of monitoring driving systems is worked out.